Information technology in foreign language education - Seitzhanova M.O. (Karagandy University of the name of acad. E.A. Buketov, 2021)
This article presents the importance of information technology in teaching foreign languages, and offers several tools for working in studies.
Keywords: reading competence; language education; foreign students; secondary school students; language difficul